A Dataset on “Social Media and India’s Foreign Policy: The Case Study of X Diplomacy During the Covid-19 Pandemic” - Mukund V. Narvenkar (Journal of Open Humanities Data)
This dataset analyzes “Social Media and India’s Foreign Policy: The Case Study of X Diplomacy during the Covid-19 Pandemic”. Collected via a web-based questionnaire targeting individuals aged 18–61+ in India, the dataset comprises 171 valid responses stored on Mendeley. It explores the significance of social media in India’s foreign policy, the influence of platforms like X in policymaking, and their effectiveness during the pandemic. Additionally, it examines how the Indian government leveraged X to communicate messages and shape narratives in international politics. This dataset offers valuable insights into social media’s impact on global diplomacy and crisis communication.